2023
DOI: 10.3390/su15042868
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices of Face Mask Use among University Students during the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: At the peak of the COVID-19 pandemic, the estimated daily use of face masks was at its highest, thereby creating huge public health and environmental challenges associated with the indiscriminate disposal of used ones. The present study assessed Abu Dhabi University students’ handling and disposal of single-use face masks during the pandemic. A cross-sectional study using an online survey questionnaire was used to gather data from 255 students from the target group. Face mask type was found to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Such precautions preserve the cleanliness of our environment and safeguard against other infections ( Kampf & Kramer, 2004 ; Wangchuk et al, 2023 ). As seen in our study, those aged 26 to 35 years showed excellent handhygiene practices when using facemasks, surpassing the other age groups could be owed to the reason that the younger generation have a better access to the informatin, awareness, education through the technical advancement and social and peer awareness and goes similar in findings with the study published among university students from Abudhabi ( Ajaj et al, 2023 ).…”
Section: Discussionsupporting
confidence: 88%
“…Such precautions preserve the cleanliness of our environment and safeguard against other infections ( Kampf & Kramer, 2004 ; Wangchuk et al, 2023 ). As seen in our study, those aged 26 to 35 years showed excellent handhygiene practices when using facemasks, surpassing the other age groups could be owed to the reason that the younger generation have a better access to the informatin, awareness, education through the technical advancement and social and peer awareness and goes similar in findings with the study published among university students from Abudhabi ( Ajaj et al, 2023 ).…”
Section: Discussionsupporting
confidence: 88%
“…Maintaining a safe distance of at least 1 meter (3 feet) from others, particularly in the crowded areas, is the recommended action to minimize the risk of COVID-19 transmission. In comparison to other groups, highly educated and competent people were found to have the decent practices (Ajaj, Shahin, Moda & Ahmed, 2023). According to statistical findings, having a private work was negatively connected to having satisfactory knowledge, whereas having a large monthly salary was positively related to having the satisfactory knowledge.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Males made up 39.1% of the participants, while females made up the remaining 60.1 percent. In this connection, the medical students were found to have the sufficient knowledge, favourable attitudes, and appropriate practises with the critical covid-19 (Ajaj, Shahin, Moda & Ahmed, 2023). Medical students frequently considered that COVID-19's eruption had had a significant impact upon their social, mental, and psychological well-being.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar observations were made in two previous studies where no practice of any form of hand hygiene before or after face mask wearing was noted among study participants. 15,16 However, it is vital to practice proper hand washing before and after wearing a face mask in daily life, so that transmission of harmful germs can be prevented from infecting yourself or other people. 17,18 In the present study, most (67.7%) participants were wearing face masks in public places to protect them against respiratory infections.…”
Section: Discussionmentioning
confidence: 99%